2019
DOI: 10.1002/suco.201800181
|View full text |Cite
|
Sign up to set email alerts
|

Seismic behavior of reinforced concrete squat walls with high strength reinforcements: An experimental study

Abstract: A total of 15 squat reinforced concrete (RC) shear walls (12 of them were reinforced with high strength reinforcement of HRB600 [Grade 600 MPa] and the remaining 3 with normal grade reinforcement of HRB400 [Grade 400 MPa]) have been tested under the cyclic loading. The influencing parameters considered in the test specimens include the grade of reinforcement, axial load ratio, types of cross section, and reinforcement ratio. The seismic performances of the squat RC shear walls have been studied using the test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Due to the complex western landscape type, mountain area is large, so the western highway railway line inevitable to cross deep gully [5,6], so the bridge often accounts for a large proportion in the line, mountain bridge using high pier can make bridge type more reasonable, economic, cost saving, in recent years some our country built or high pier bridge under construction. With the implementation of the strategy of the western development policy, so the high pier bridge to face the seismic problem is more prominent [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex western landscape type, mountain area is large, so the western highway railway line inevitable to cross deep gully [5,6], so the bridge often accounts for a large proportion in the line, mountain bridge using high pier can make bridge type more reasonable, economic, cost saving, in recent years some our country built or high pier bridge under construction. With the implementation of the strategy of the western development policy, so the high pier bridge to face the seismic problem is more prominent [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The test results showed that the T‐shaped shear walls had better ductility than traditional RC shear walls. Chen et al 15 investigated the seismic behavior of the T‐shaped shear wall with high‐strength reinforcement, and the failure mode showed that the T‐shaped specimen failed in the form of brittle concrete crushing at the ends without flange elements. In terms of the hysteresis behavior, load carry capacity, and ultimate drift ratio, the seismic behaviors of T‐shaped shear walls reinforced with high‐strength reinforcement are similar to that of the walls with normal strength reinforcement, even when the amount of reinforcement was decreased by around 30% due to the use of high‐strength reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing contribution of steel fibers can be mobilized in planar SFRC elements, such as elevated SFRC slabs, as the primary reinforcement 29 . Many studies conducted, in recent years, on the specifications and characteristics of fiber reinforced concrete, including the effects of volume, aspect ratio, geometry, alignment and resistance of fibers 30–44 . Most studies have been focused on concrete technology and structural components such as beams, columns and connections.…”
Section: Introductionmentioning
confidence: 99%